DETERMINANTS OF DEBT RESCHEDULING IN EASTERN EUROPEAN COUNTRIES - Laušev, Jelena; Stojanović, Aleksandar; Todorović, Nataša (Economic Annals, 2011)
This study utilizes Panel Logit Models applied to a set of macroeconomic, financial, and political variables to estimate the debt rescheduling probabilities of 15 Eastern European countries during the transition period from 1990-2005. These transition economies became a very attractive region for foreign investment. Specifically, the region became the largest recipient of net non-FDI flows among all emerging market regions in 2005. Therefore, it is relevant for policy makers and institutional and private foreign investors to investigate factors that influence debt rescheduling probabilities, as these may directly affect the size of and return on investments in these countries. Our findings suggest that policy efforts focused on reducing government expenditure, attracting foreign direct investment, increasing export revenues, and keeping a good repayment record result in low debt rescheduling probabilities and, in turn, decrease the cost of debt for these countries. This is a common finding for all countries in the sample, including those that have become EU members.